Perceptions of midwives regarding their role in childbirth at hospitals from Porto Alegre - Jéssica Teles Schlemmer; Luane Moreira de Aguiar; Mirela de Sousa Nunes Duarte; Fernanda Peixoto Córdova; Aline Alves Veleda (Revista Gaúcha de Enfermagem)
ABSTRACT Objectives: To understand the perceptions of obstetric nurses (midwives) about the work dynamics in the parturition process at hospitals from Porto Alegre/Rio Grande do Sul. Method: Exploratory-descriptive study with a qualitative approach with 12 midwives Who worked at eight obstetric centers in the city, recruited using the snowball technique. Data collection was carried out by the application of a semi-structured instrument and electronically, from September to November of 2023. The data analysis technique was thematic. Results: Midwives realize that their performance contributes to the rescue of physiological birth. The work of midwives in households was replaced by a non-collaborative and often interventionist model. Administrative demands, the staffing framework, and the relationships between professionals appear as factors that hinder the insertion of nurses in childbirth care. Final considerations: The legislation does not guarantee autonomy to provide birth assistance. Implications for practice are the need for managers committed to implementing the collaborative birth care model and review in staffing for full autonomy of midwives in this scenario.